Implementasi Metode Time Invariant Fuzzy Time Series Untuk Memprediksi Jumlah Keberangkatan Penumpang Pelayaran Dalam Negeri Di Pelabuhan Tanjung Priok - Dwi Damara Kartikasari; Budi Darma Setiawan; Mochammad Ali Fauzi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Maritime transportation is considered to have an important contribution in advancing the national economy in Indonesia, considering that 75% of Indonesia's territory is in the ocean. Maritime transportation has also become an alternative of transportation between islands recently. Moreover with the increase in the number of vehicles on land from year to year resulting in congestion on the highway, of course this will further increase public interest in making maritime transportation an alternative to their transportation. But in every cruise, the number of passengers always decreases or increases. The uncertainty of the number of passengers must be predictable, so that further policies can be made from the port to anticipate the number of passengers in the future, in order to increase economic benefits in the sea transportation sector. The method used to make predictions in this research is Time Invariant Fuzzy Time Series with the data used is the number of cruise passenger departures at Tanjung Priok Port in the period January 2006 to December 2015. Based on the results of the test, the smallest of Mean Average Percentage Error (MAPE) is 17.39% using the number of fuzzy sets = 5; training data = 108, 96, 84, and testing data = 12.